Ceritinib-induced regression of an insulin-like growth factor-driven neuroepithelial brain tumor - Russo, Alexandra; Burhenne, Jürgen; Fresnais, Margaux (International journal of molecular sciences, 2019)
The insulin-like growth factor (IGF) pathway plays an important role in several brain tumor entities. However, the lack of inhibitors crossing the blood–brain barrier remains a significant obstacle for clinical translation. Here, we targeted the IGF pathway using ceritinib, an off-target inhibitor of the IGF1 receptor (IGF1R) and insulin receptor (INSR), in a pediatric patient with an unclassified brain tumor and a notch receptor 1 (NOTCH1) germline mutation. Pathway analysis of the tumor revealed activation of the sonic hedgehog (SHH), the wingless and integrated-1 (WNT), the IGF, and the Notch pathway. The proliferation of the patient tumor cells (225ZL) was inhibited by arsenic trioxide (ATO), which is an inhibitor of the SHH pathway, by linsitinib, which is an inhibitor of IGF1R and INSR, and by ceritinib. 225ZL expressed INSR but not IGF1R at the protein level, and ceritinib blocked the phosphorylation of INSR. Our first personalized treatment included ATO, but because of side effects, we switched to ceritinib. After 46 days, we achieved a concentration of 1.70 µM of ceritinib in the plasma, and after 58 days, MRI confirmed that there was a response to the treatment. Ceritinib accumulated in the tumor at a concentration of 2.72 µM. Our data suggest ceritinib as a promising drug for the treatment of IGF-driven brain tumors.
Gesehen am 23.12.2019